OP89 Pre-pregnancy and postnatal depressive symptoms are associated with quality of mother-child relationships; longitudinal data from the southampton women's survey. (2nd September 2017) - Baird, J; Barker, M; Lawrence, W; Kendrick, T; Crozier, S; Robinson, SM; Cooper, C; Godfrey, KM; Inskip, HM
Abstract : Background: Maternal mental health difficulties have been associated with poor outcomes for children, possibly because they affect the quality of the relationship between mother and child. We examined associations between maternal depressive symptoms before pregnancy, and again 6 months postnatally, and quality of the mother-child relationship in the Southampton Women's Survey (SWS). Methods: The SWS is a population based cohort study of 12 583 women aged 20–34 years who were assessed when not pregnant; those enrolled during the latter half of the recruitment period completed the General Health Questionnaire (GHQ-12), a short screening instrument with good sensitivity for depression and anxiety disorders. Women who became pregnant and their children (n=3158) were followed up. Six months post-partum, mothers completed the Edinburgh Postnatal Depression Scale (EPDS) questionnaire to determine depressive symptoms. Established cut-offs for each scale were used to determine the presence or absence of depressive symptoms at the two time points. A summary pre-pregnancy and postnatal depressive symptoms 4-level categorical variable was derived indicating symptoms at neither, one or other, or both periods. When the child was 3 years old, mothers completed the Pianta Child-Parent Relationship Scale (CPRS), from which closeness and conflict scores were derived. To normalise these scores a Fisher-Yates transformation was used so that the scores are presented in standard deviation (SD) units. Linear regression was used to relate the two mother-child relationship measures to depressive symptoms, adjusting for confounding factors identified using a Directed Acyclic Graph: receipt of benefits, employment, parity and educational attainment. Results: Among women with GHQ-12 and EPDS data, 1441 completed the Pianta CPRS. Presence of depressive symptoms was identified before pregnancy in 28% of mothers and postnatally in 42%. After adjustment for confounders, and compared with those with no symptoms during either time period, those who only had depressive symptoms postnatally had conflict scores that were elevated by 0.28SD (95% CI: 0.16–0.41), whereas scores for those with depressive symptoms at both time periods were elevated by 0.53SD (95% CI: 0.39–0.68). Closeness scores were reduced in those with symptoms at both time periods, being 0.26SD (95% CI: 0.08–0.43) lower than for those with no symptoms, but were not reduced in those with depressive symptoms at one or other period only. Conclusion: Women who suffer from depressive symptoms both before and after pregnancy appear vulnerable to poorer relationships with their children. This emphasises the importance of maternal mental health for the mother and for her relationship with her child.